Enredamentos: o constituir nacional entre Portugal e Brasil nas cortes de Lisboa (1820-1822) - Alexandre Bellini Tasca (2016)
The purpose of this dissertation is to contribute to the understanding of the role of discourse in political practice throughout the process of national formation of Portugal and Brazil. To do so, it will examine the Extraordinary and Constitutional General Courts of the Portuguese Nation, which took place between January 1821 and November 1822, as consequence of the events that took place on August 24, 1820, at the city of Porto. Guided by a liberal ideology, heir to the illustrated thought that gained strength in eighteenth-century Europe, events of this sort have spread across the globe, the American Revolution of 1776 and the French Revolution of 1789 being the ones that have achieved greater prominence. On both sides of the Atlantic Ocean, the Ancient Regime structures showed signs of its exhaustion: the concentration of power in the hands of a sovereign monarch being a prime example of this. Thus, the Courts, exercising the legislative power, appear as an institution of these new times par excellence. For the first time in History a significant portion of the inhabitants of the Portuguese domains could elect deputies who, in Lisbon, would represent them, debating and developing laws that should be valid in all areas of the Portuguese Nation. Within this context, uncertainties and fluidity prevailed and the very understanding of what nation should be lacked clear definitions. Interweaving the history of both Portugal and Brazil, this analysis will begin by examining the definition of what Fernando Catroga called Empire Nation State and its byproducts. Furthermore, several aspects related to the discourses converging or competing with each other with such imperial pretensions will be analyzed, among which are: "sovereignty", "the oath", "representation" and "experience".